Trombosis venosa profunda en pacientes intervenidos quirúrgicamente por patología de cadera. Hospital Carlos Andrade Marín. - Flores Fuentes, Stephanie Carolina (2019)
The first time phrase Deep Vein Thrombosis (DVT) was used, it was in a manuscript by Guillaume de Sain Pathus in the 13th century, he described the case of a young man from Normandy, DVT is a pathology that is induced by obstruction of venous light by a thrombus of fibrin and red blood cells (DIAZ, 2018). In our country there are a few studies, it is estimated that there is a incidence of 1 per 1000 inhabitants (BASANTES,2014), while without prophylaxis in total hip prostheses it has an incidence of 50-60%, in addition in a study carried out in San José de Bogotá hospitals, it presented 1,69% of frecuency leading the postsurgical complications (MOSQUERA C, RUEDA G, CABEZA C, TOBAR J Y ARMANDO HUGO, 2017). The risk of acaquiring DVT is mainly correlated with the following risk factors, older ago, obesity, prolonged immobilization, a history of orthopedic surgeries and interventions longer that two hours. The use of correct prophylaxis by means of the Caprini, Wells and Padua scale, together with the appropriate choice of medication it has reduced its incidence globally. Our study focuses on a universe of 131 people, excluding pediatric population, patiens with a history of DVT, pregnant woman and in the puerperium, from which 2 patients who developed this disease were obtained, the risk factores shared were also analyzed, in which age older that 40 years, current sugery longer that 2 hours and a history of orthopedic surgery stand out. The Caprini scale is the most used in HECAM, mechanical and pharmacological prophylaxis are fundamental pillars, but when analyzing by subgroups it can be pointed out thata the percentage of patients stratified as high risk who did not receive pharmacological prophylaxis, at the pre surgical moment is 35.11%, in the postoperative period 4.58% an 4.58% in outpatients.